2022
DOI: 10.1038/s41467-022-34422-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics signatures of the human early life exposome

Abstract: Environmental exposures during early life play a critical role in life-course health, yet the molecular phenotypes underlying environmental effects on health are poorly understood. In the Human Early Life Exposome (HELIX) project, a multi-centre cohort of 1301 mother-child pairs, we associate individual exposomes consisting of >100 chemical, outdoor, social and lifestyle exposures assessed in pregnancy and childhood, with multi-omics profiles (methylome, transcriptome, proteins and metabolites) in childhood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 116 publications
2
38
0
Order By: Relevance
“…As such, the proteome and metabolome are the closest omics to phenotype (and thus, perhaps most useful as a biomarker of disease risk or prognosis) but also exhibit the most interand intra-individual variability (Gallego-Paüls et al, 2021), thereby making replication and validation more challenging. However, result consistency across layers, if it occurs, reinforces causality, as we demonstrated in our recent multi-omics study of the early life exposome (Maitre, Bustamante, et al, 2022).…”
Section: Quality Of Evidence and Risk Of Biassupporting
confidence: 80%
“…As such, the proteome and metabolome are the closest omics to phenotype (and thus, perhaps most useful as a biomarker of disease risk or prognosis) but also exhibit the most interand intra-individual variability (Gallego-Paüls et al, 2021), thereby making replication and validation more challenging. However, result consistency across layers, if it occurs, reinforces causality, as we demonstrated in our recent multi-omics study of the early life exposome (Maitre, Bustamante, et al, 2022).…”
Section: Quality Of Evidence and Risk Of Biassupporting
confidence: 80%
“…Furthermore, epigenetics might play a role in connecting the environments to PTB (70) . A multi-omics study found that maternal Mo exposure during pregnancy was related to the methylation levels of 72 CpGs representing sixty-three loci, and thirteen of them have previously been related to gestational age (71) . Another study suggested that maternal Cd exposure was associated with a decrease in gestational age through an alteration in DNA methylation at a specific CpG site, cg21010642 (72) .…”
Section: Discussionmentioning
confidence: 99%
“…This integration has not been achieved before IDSL.GOA since there was not a single knowledgebase developed that have created the GO-term specific focused reaction networks. IDSL.GOA can also support the statistical multi-omics analysis to extract meaningful biological information from correlated features across multiple omics datasets 31 . By integrating the results of IDSL.GOA with the results of statistical multi-omics analysis, researchers can obtain a more comprehensive understanding of the underlying biological mechanisms that are involved in the disease or condition of interest.…”
Section: Discussionmentioning
confidence: 99%